Analisis Daerah Potensi Longsor Menggunakan Metode Geolistrik Resistivitas di Danau Kastoba Pulau Bawean Indonesia - Karimah Karimah; Adi Susilo; Eko Andi Suryo; Aunur Rofiq; Muhammad F.R. Hasan (Jurnal Penelitian Pendidikan IPA, 2022)
Kastoba Lake in Bawean Island Indonesia is a tourist attraction that has a level of vulnerability in landslide disasters. The landslides has been happen. From the large and small scale in the Kastoba Lake. Base on the problem, the landslides occured due to the field of derailment. According to the above statement, it was necessary to know the subsurface structure and the field of avalanche derailment in the kastoba lake area. This data was allowed by geophysical resistivity method which a dipole-dipole configuration with 4 measurement points. The acquisition of data was based on preliminary studies from the analysis of landslide vulnerability level maps (DEM Alos data processing) that have been done first. The results of lithological analysis with geoelectric resistivity methods in this research obtained three layers of subsurface structure, namely top soil (top layer) with a resistivity value of 7-110 Î©m, clay (middle layer) which was a resistivity value of 110-210 Î©m and lava (bottommost layer) which was a resistivity value of 210-357 Î©m. The field of gelincir in the research area was on the top layer of soil composed of weathering of rocks mixed with organic material or leaf/tree decay with an average depth of 7.25 meters. Thus, this research can be one of the parameters of landslide disaster mitigation in the development of geotourism in Kastoba Lake